Impact of interventions by consortium for improving agriculturebased livelihoohds in Central Africa (CIALCA) on food and nutrition security of farmer households - Ekesa, B.; Lange, M. de; Macharia, I.; Garming, H.; Ouma, Emily A.; Birachi, Eliud Abucheli; Asten, Piet J.A. van; Vanlauwe, Bernard; Blomme, Guy (2013)
Impact of adopting products promoted by the Consortium for Improving Agriculture-based livelihoods in Central Africa (CIALCA) on food and nutrition security was tested. Multistage sampling was used to select 7 project mandate areas, 5 villages/mandate area (stratified into action, satellite and control sites) and 913 households. Structured questionnaires were administered; analysis of impact based on comparison between stratums, differences in means tested by ANOVA and significance of difference obtained by Tukey's HSD multiple rank tests. Perception of adequate food sufficiency received a higher rating in action and satellite sites compared to control sites reason being improved agricultural technologies. For >60% of households, worsened food security was due to climatic conditions. Although a higher proportion of households in action and satellite was meeting calorie RDIs in DRC and Burundi the difference was insignificant from control sites. 53% of respondents in control sites indicated a decrease in intake of protein rich foods, this was significantly higher than the proportion in the action (46%) and satellite (41%) sites.